A Highly Efficient and Recyclable Pd(Pph3)4/Peg-400 System for Stille Cross-Coupling Reactions of Organostannanes with Aryl Bromides. (September 2017) - Huang, Xue; Yao, Fang; Wei, Ting; Cai, Mingzhong
Pd(PPh3 )4 in PEG-400 is shown to be a highly efficient catalyst for the Stille cross-coupling reactions of various organotin compounds with aryl bromides. The reaction could be conducted at 80 °C using NaOAc as base, yielding a variety of biaryls, alkynes and alkenes in good to excellent yields. The isolation of the products was readily performed by extraction with petroleum ether and the Pd(PPh3 )4 /PEG-400 system could be easily recycled and reused five times without any significant loss of activity.